Why and how to resolve the illegality of the 1970 election and the 1971 constitutional convention in the Philippines - Rosario, Simeon G. del (Quezon City SGR Research & Publishing, 1971)
94 p. ; 23 cm.
1
Keywords: Elections -- Philippine Islands; Constitutional conventions -- Philippine Islands; Philippine Island -- Elections; Philippine Islands -- Constitutional conventions